The relative importance of looks, height, job, bio, intelligence, and homophily in online dating: A conjoint analysis - Jessika Witmer; Hannes Rosenbusch; Erdem O. Meral (Computers in Human Behavior Reports)
Researchers have forwarded many attributes that boost (or impede) dating success, but rarely quantify their relative importance in real dating scenarios. Here, we observed matching decisions of hetero- and bisexual online daters to isolate the simultaneous effects of targets' physical attractiveness, height, job, intelligence, biography, as well as selector X target homophily. A conjoint analysis of 5340 “swiping” decisions by 445 online daters demonstrated an overwhelming importance of physical attractiveness for dating success. A one SD improvement in physical attractiveness boosts one's selection success by around 20%, while the same increase in intelligence only improves one's chances by 2%. While this field study replicates and concretizes many laboratory findings, our conjoint attribute evaluation also showed that men and women had equal priorities and attribute effects, opposing some common hypotheses in the field. Further, the causal effects of intelligence, height, bio, occupation, and self-reported homophily were literature-consistent, but 7 to 20 times smaller than the effect of attractiveness. Implications for studying dating decisions, as well as practical considerations for designing dating profiles and apps, are discussed.